Rasgos personológicos, su incidencia en la formación del perfil profesional de una estudiante de pregrado de la carrera de Educación Básica - Litardo Vásconez, Dennis Enoc (2019)
Society currently demands a quality education with values, this transcendental slogan falls on teachers, to form generations with the capacity to generate a change in their environment to improve every day. It is so important to establish which the incidence of personological traits in the professional formation of the Faculty of Legal Sciences Basic Education career, Social and Education at the Technical University of Babahoyo to carry out a qualitative analysis of the real profile and to promote the profile of students with aptitude and motivation with a greater vocation. To this end, interview and observation techniques have been used, resulting in the solution proposed, which was to consider personality traits suitable for pursuing a career such as: emotional balance, values, service vocation and positive skills, all necessary for optimal career performance.